Why is cytoskeletal contraction required for cardiac fusion before but not after looping begins?. (30th January 2015) - Shi, Yunfei; Varner, Victor D; Taber, Larry A
Abstract: Cytoskeletal contraction is crucial to numerous morphogenetic processes, but its role in early heart development is poorly understood. Studies in chick embryos have shown that inhibiting myosin-II-based contraction prior to Hamburger–Hamilton (HH) stage 10 (33 h incubation) impedes fusion of the mesodermal heart fields that create the primitive heart tube (HT), as well as the ensuing process of cardiac looping. If contraction is inhibited at or after looping begins at HH10, however, fusion and looping proceed relatively normally. To explore the mechanisms behind this seemingly fundamental change in behavior, we measured spatiotemporal distributions of tissue stiffness, stress, and strain around the anterior intestinal portal (AIP), the opening to the foregut where contraction and cardiac fusion occur. The results indicate that stiffness and tangential tension decreased bilaterally along the AIP with distance from the embryonic midline. The gradients in stiffness and tension, as well as strain rate, increased to peaks at HH9 (30 h) and decreased afterward. Exposure to the myosin II inhibitor blebbistatin reduced these effects, suggesting that they are mainly generated by active cytoskeletal contraction, and finite-element modeling indicates that the measured mechanical gradients are consistent with a relatively uniform contraction of the endodermal layer in conjunction with constraints imposed by the attached mesoderm. Taken together, our results suggest that, before HH10, endodermal contraction pulls the bilateral heart fields toward the midline where they fuse to create the HT. By HH10, however, the fusion process is far enough along to enable apposing cardiac progenitor cells to keep 'zipping' together during looping without the need for continued high contractile forces. These findings should shed new light on a perplexing question in early heart development.